НАБЛЮДАТЕЛЬНАЯ РСДБ-СЕССИЯ RAPL02. РЕЗУЛЬТАТЫ ОБРАБОТКИ ДАННЫХ - Чуприков A. А. (Одеські астрономічні публікації, 2011)
Results of processing of data of a VLBI experiment titled RAPL02 are presented. These observations were made in 2011 February with 5 antennas. All 3 antennas of Petersberg’s Institute of Applied Astronomy (IAA) were used in this session. These were antennae in Svetloe, in Zelenchuck, and in Badary. Additionally, a 22-m antenna in Puschino as well as a 32-m antenna in Medicina (Italy) were also included into observations. The raw data correlation was made at the software correlator of Astro Space Center. The secondary data processing was made for 3 quasars, 3C273, 3C279, and 3C286.